Agronomic system for stabilizing wheat yields and enhancing the sustainable utilization of soil: A 12-year in-situ rotation study in a semi-arid agro-ecosystem. (20th December 2021) - Wu, Peng; Zhao, Gang; Liu, Fu; Ahmad, Shakeel; Fan, Tinglu; Li, Shangzhong; Zhang, Jianjun; Dang, Yi; Wang, Lei; Wang, Shuying; Cheng, Wanli; Cai, Tie
Abstract: Continuous wheat ( Triticum aestivum L.) cropping in the Loess Plateau of China has led to soil degradation and yield reductions. In the present study, we conducted a long-term wheat rotation experiment in Zhenyuan County, Gansu Province, China, between 2005 and 2017, where three cropping systems were tested: (1) continuous winter wheat cropping (W), (2) wheat–wheat–wheat–soybean, i.e., 3 years of wheat and 1 year of soybean ( Glycine max L . ) rotation (W3–S), and (3) wheat–wheat–wheat–maize, i.e., 3 years of wheat and 1 year of maize ( Zea mays L . ) rotation (W3-M). Equal amounts of fertilizer were applied to all treatments. All treatments were conducted for four years and repeated three times, with a total of 12 years. Continuous wheat cropping increased the soil bulk density and decreased the soil porosity compared with 2005. However, W3–S and W3-M significantly reduced the soil bulk density and increased the soil nutrients and enzyme activities in 2017 compared with continuous wheat cropping. The average increases in the soil water storage under W3–S and W3-M were 12.7% and 5.9%, respectively. During the wheat growing season, the water use efficiencies under W3–S and W3-M were 22.9% and 12.9% higher, respectively, than that under continuous wheat cropping. The average wheat yields under W3–S and W3-M increased by 25.1% and 14.1%, respectively. Furthermore, according to principal component analysis and correlation analysis, the yield increases were due to the enhanced soil quality, enzyme activities, and water use efficiency. These results suggest that rotation can enhance the soil properties, soil enzyme activity, crop yield, and soil water use efficiency. In addition, wheat–soybean rotation had more positive effects than wheat–maize rotation on the soil quality and crop productivity in the study area. However, wheat was not produced in the fourth year of rotation so the replacement crop would need to be economically viable to facilitate widespread adoption. Further investigation is also required to determine whether the lower biomass production associated with legumes was offset by the increased soil organic carbon during the wheat phase of the rotation. The best rotation method identified in this study may provide a cleaner agronomic production strategy. Highlights: Soil bulk density increased under long-term continuous wheat cropping. Rotation significantly reduced soil bulk density, increased soil porosity, and increased SOC when same inputs applied. Rotation enhanced soil nutrients and enzyme activities to increase crop yields. Wheat–soybean rotation had more positive effects on soil quality and crop productivity than wheat–maize rotation.